Teamwork in Health Care Services Delivery in Nigeria: A Mixed Methods Assessment of Perceptions and Lived Experiences of Pharmacists in a Tertiary Hospital - Mohammed E; McDonald WG; Ezike AC (Dove Medical Press, 2022)
Elijah Mohammed,1,2 Warren G McDonald,1 Adaobi C Ezike3 1Department of Health Policy, Walden University, Baltimore, MD, USA; 2Department of Registry, Pharmacists Council of Nigeria, Abuja, Nigeria; 3Department of Pharmacology and Toxicology, University of Nigeria, Nsukka, Enugu State, NigeriaCorrespondence: Adaobi C EzikeDepartment of Pharmacology and Toxicology, University of Nigeria, Nsukka, 410001, Enugu State, NigeriaTel +234 80 5282 0538Email adaobi.ezike@unn.edu.ngBackground: Lack of teamwork is the bane of weak and ineffective health care systems in many countries. This study examined the perceptions and lived experiences of pharmacists working in a Nigerian government-owned (public) multispecialty tertiary hospital regarding teamwork in their workplace.Methods: A sequential explanatory mixed methods study using phenomenological approach of inquiry, was conducted among pharmacists with experience in multidisciplinary health care provision in a public tertiary hospital in Nigeria. Questionnaires with 16 close-ended questions based on a Likert scale, which scored from strongly disagree (1) to strongly agree (5), were administered. The mean (M) scores were determined using SPSS Version 20; M ≥ 3.00 indicated agree, while M < 3.00 disagree. Subsequently, focus group discussions were conducted, and the audio recorded responses transcribed and subjected to thematic analysis using NVivo 11.Results: Some participants (50%) had worked for 5- 10 years in the hospital's Department of Pharmacy, 25% (11- 20 years), and 16.7% (21- 30 years). Participants agreed that effective teamwork leads to positive patient outcomes (M = 3.67) and is in the public's interest (M = 4.25). However, they disagreed that their workplace supports teamwork (M = 2.33), effective interprofessional collaborative practices exist in the hospital (M = 1.08), and their remuneration reflects their worth to the organization (M = 2.33). Doctors' dominance and claim of ownership of patients, allied professionals' attitudes and ignorance of pharmacists' roles, salary disparity, poor communication, and defective leadership style among others were identified as impediments to teamwork.Conclusion: The hospital pharmacists demonstrated positive disposition towards teamwork, and agreed that effective teamwork would improve health care delivery. However, they identified some factors that hinder interprofessional teamwork in the hospital. Principles and practices of teamwork should be incorporated into the curriculum of each discipline; interdisciplinary collaborative practices, health system structure, institutional policies and leadership should be strengthened to enhance teamwork.Keywords: attitudes of health care professionals, interprofessional collaboration, ownership of patients, interdisciplinary rivalry, turf protection, salary disparity